Weight history of individuals with and without physical disability in the International Weight Control Registry - Julianne G. Clina; R. Drew Sayer; Anna M. Gorczyca; Sai Krupa Das; James E. Friedman; Tsz Kiu Chui; Susan B. Roberts; James O. Hill (Wiley, 2024)
Abstract Background People with physical disabilities (PWD) have an increased risk of obesity and related comorbidities compared with people without physical disabilities (PWoD). Previously identified contributors to weight loss maintenance pose challenges to PWD. However, it is not known if PWD experience less success in weight management. Methods Six hundred and nine participants in the International Weight Control Registry (IWCR) were eligible for this analysis (PWD, n = 174; PWoD, n = 435). Self‐reported weight history metrics were compared using general linear models. Perceived weight history category was compared using Chi‐squared tests. Importance of diet and physical activity strategies for weight management were compared using Wilcoxon rank‐signed tests. Results PWD reported higher current body mass index (BMI) (36.1 ± 0.7 vs. 31.0 ± 0.5; p < 0.0001) and more weight loss attempts (9.1 ± 0.7 vs. 7.1 ± 0.4; p = 0.01) than PWoD. Current weight loss percentage (PWD 13.0 ± 1.0; PWoD, 13.0 ± 0.6; p = 0.97) and weight loss category (χ2 [3, N = 609] = 2.9057, p = 0.41) did not differ between the groups. There were no differences in any weight strategy between PWD who were successful and those who regained. Conclusions PWD and PWoD in the IWCR achieved similar levels of weight maintenance success. However, higher BMI and more weight loss attempts suggest that PWD may face challenges with weight management. More research is needed to identify strategies leading to success for PWD.